Characterization of multidrug-resistant and extended-spectrum beta-lactamase-producing Klebsiella pneumoniae strains from Malaysian hospitals - Lim, K.T.; Yeo, C.C.; Yasin, R.M.; Balan, G.; Thong, Kwai Lin (Microbiology Society, 2009)
The emergence of multidrug-resistant (MDR) and extended-spectrum beta-lactamase (ESBL)-producing Klebsiella pneumoniae poses a serious antibiotic management problem as resistance genes are easily transferred from one organism to another. Fifty-one strains of K. pneumoniae isolated from sporadic cases in various hospitals throughout Malaysia were analysed by antimicrobial susceptibility testing, PCR detection of ESBL-encoding genes and DNA fingerprinting. Although 27 of the 51 K. pneumoniae strains were MDR (i.e. resistant to three or more classes of antibiotics), the majority of the strains (98 %) were sensitive to imipenem. PCR detection using ESBL gene-specific primers showed that 46 of the K. pneumoniae strains harboured bla(SHV), 19 harboured bla(CTX-M), 5 harboured bla(OXA-1) and 4 harboured bla(TEM-1). Class 1 integron-encoded intI1 integrase was detected in 21 of the 51 K. pneumoniae strains and amplification of the integron 5'CS region showed the presence of several known antibiotic resistance gene cassettes of various sizes. Results of conjugation and transformation experiments indicated that some of the ESBL-encoding genes (i.e. bla(SHV), bla(CTX-M) and bla(TEM-1)) were transmissible and were likely plasmid-encoded. DNA fingerprinting using PFGE and PCR-based methods indicated that the 51 K. pneumoniae strains were genetically diverse and heterogeneous.